Implementing digital health transformation policies in Latin America: insights from four national case studies - Paola Abril Campos Rivera; Pablo Villalobos Dintrans; Berenice Alfaro-Ponce; Beatriz Michelle Ramírez Pérez; Daniel Choperena; Adolfo Rubinstein; Cintia Cejas; Felix Liberona; Michael R. Reich (npj Digital Medicine, 2026)
Abstract Digital health transformation (DHT) policies can improve the performance of health systems. However, there are few empirical studies on how these policies are implemented in practice. This article examines four national cases of implementing DHT policies in the Latin American region. The study employs a qualitative methodology based on 32 semi-structured interviews and a multiple case study approach in Uruguay, Argentina, Chile, and Mexico—selected for their diversity in governance structures and different stages of digital health transformation. It uses in-depth context-specific qualitative analysis to identify key factors in DHT policy implementation. The study shows that the interaction of policy objectives, technical and financial conditions, organizational and political dynamics, and implementation capacities was relevant for DHT implementation. Clear definitions of problems, coherent and context-sensitive implementation strategies, strong multisectoral teams, sustained leadership, capacity-building efforts, and robust governance frameworks all played critical roles in promoting implementation. The results suggest that effective DHT implementation depends not only on technical aspects of the policy but also on the coherence and institutional adoption of clear policy objectives in different contexts. The study shows how DHT implementation should be viewed as a strategic means to improve health system performance—rather than an end in itself.